Analisis Optimalisasi Sistem Antrian dengan Model M/M/S pada Perbankan - Thabrani, Gesit; Rahmiati, Rahmiati; Wirma, Rizky Weindra (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2017)
The purpose of this research is to analyze (1) How is the performance of a queuing system that is currently used in the transaction process in the Bank Nagari Cabang Pembantu Unand (2) How to optimize the model M / M / S on Bank Nagari Cabang Pembantu Unand. The results showed that: (1) The performance of Bank Nagari Cabang Pembantu Unand conditions busy hours (10:00 to 12:00) is not optimal it can be seen from unfulfilled time standards target (2) The Proper number of teller on Bank Nagari Cabang Pembantu Unand for busy hours are 3 teller, with the time average to serve 1 customers reduced from 7 minutes to 2 minutes, and it is fulfilled the time standard targets.